ANTROPOLOGI EKONOMI : MASYARAKAT MEYBRAT DI KEPALA BURUNG PAPUA BARAT - Arius A. Kambu (Universitas Cenderawasih, 2014)
The purpose of this study is to explain in depth and thorough about the value of kinship and consumptive pattern that gives a clear impact on the pattern of the business establishment of Meybrat people. The sample access is all kinds of Meybrat people's business. This study used a qualitative analysis of a single case study approach. The results of this study found that (1) the business of Meybrat people is still at the stage of looking for shapes (innovation , triggering) where the personal character (personal values, education, experience, risk taking, internal control) are still weak in shaping the behavior of Meybrat people's business; (2) business groups (micro, small and medium enterprises) are more successful and grow well on an individual level than on groups; (3) Factors of kinship consumptive pattern systems and communities include: payment of dowry, families and relatives' education costs which is still a strong influence in shaping the conduct of business of Meybrat people. Keywords: Kinship, Consumer Pattern, Productive Economy